UNLOCKING EXPRESSION: TASK-BASED INSTRUCTIONS FOR REPRODUCTIVE SKILLS IN EFL - Maftuna Abdurasulova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the transformative impact of task-based instructions in unlocking and fostering expressive proficiency within the realms of English as a Foreign Language (EFL) education. Through a comprehensive examination of theoretical foundations, practical methodologies, and the tangible outcomes observed, the article sheds light on the efficacy of task-based approaches in cultivating reproductive skills, ultimately enhancing language learners' ability to express themselves confidently in both written and spoken forms.